Juridical Analysis About Cyberbullying Cases by Child Perpetrators Against Child Victims - Joshua Evandeo Irawan; Andrian Nathaniel; Steven Jonathan (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
This study discusses the legal protection of a child victim of cyberbullying and a child perpetrator. This research raised a case where a child with the initial “Z” who became a victim of cyberbullying from her schoolmate with the initial “S”. The research method used is the normative-juridical method: processing legal materials collected through a literature review.This study aims to determine the applicable law (legal protection) against the child victims of cyberbullying, based on Law No.35 of 2014 in conjunction with Law No.11 of 2008. In terms of the child perpetrator of cyberbullying, the criminal justice system of the children must be based on Law No. 11 of 2012.The result shows that “Z”, the child victim of Cyberbullying, has received positive legal protection in Indonesia based on Article 76C of Law 35/2014, and Article 27 paragraph (4) juncto Article 28 paragraph (2) of Law 11/2012. Child “S” who terrorizes Child “Z” via WhatsApp may be subject to criminal sanctions in accordance to Article 80 paragraph (1) of Law 35/2014 juncto Article 45 paragraph (1) and (2) of Law 11/2008 junctis Article 81 of Law 11/2012. This case criminal sanctions can be imposed on Child “S” with Law 11/2012.